1995
DOI: 10.1007/bf00177783
|View full text |Cite
|
Sign up to set email alerts
|

Passage of drugs through different intraocular microdialysis membranes

Abstract: We have shown that the above-mentioned substances penetrate into the vitreous body of rabbits through an implanted microdialysis membrane. This is of importance for the development of new means of intraocular drug administration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

1997
1997
2000
2000

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…With microdialysis the administration can be repeated several times as long as the intraocular membrane functions. In previous experiments with chronically implanted intraocular probes, the membranes regularly stayed functional for 3 weeks or more (Waga et al 1991;Waga & Ehinger 1995). Other investigators using removable intraocular microdialysis probes repeatedly introduced through a scleral port, report no complications for up to 6 months (Stempels et al 1993).…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…With microdialysis the administration can be repeated several times as long as the intraocular membrane functions. In previous experiments with chronically implanted intraocular probes, the membranes regularly stayed functional for 3 weeks or more (Waga et al 1991;Waga & Ehinger 1995). Other investigators using removable intraocular microdialysis probes repeatedly introduced through a scleral port, report no complications for up to 6 months (Stempels et al 1993).…”
Section: Discussionmentioning
confidence: 84%
“…The reason for this was to compare the measured concentration in the buffer with the concentration in the vitreous after an in vivo perfusion. For the in vivo experiments, a microdialysis probe with a 6 mm PES membrane bent for ocular use (Waga & Ehinger 1995) was implanted into the vitreous of both eyes of anesthetized pigmented rabbits. M. In the latter case the labeled NGF was used as a tracer mixed with an unlabeled carrier (Sigma).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Every other day, the condition of the implanted membrane was checked by a perfusion with [ 3 H]H 2 O, like we have done in our previous series (Waga et al 1991(Waga et al , 1995(Waga et al , 1997.…”
Section: Retrodialysis For Concentration Monitoring In the Vitreousmentioning
confidence: 99%
“…It has been adapted for ocular use in chronic experiments (Waga et al 1991). We have shown that it can be used for chronic administration of certain drugs into the rabbit vitreous (Waga & Ehinger 1995). This study aims to investigate the possibility of administrating ganciclovir into the rabbit vitreous by microdialysis.…”
mentioning
confidence: 99%